Additive Consistency and Group Decision-Making Consensus Analysis of Hesitant-Intuitionistic Fuzzy Preference Relations - Xue Feng; Sheng Ling Geng; Yong Ming Li (Journal of Mathematics)
The paper addresses the group decision-making (GDM) problem involving hesitant-intuitionistic fuzzy preference relations (HIFPRs), focusing on additive consistency and group consensus analysis. Firstly, to preserve the original decision information effectively, the consistency improvement algorithm is designed to identify decision information requiring modification and subsequently execute a localized adjustment process. Secondly, an algorithm is developed to derive HIFPRs that satisfy both acceptable consistency and group consensus simultaneously. Additionally, an approach for calculating decision-maker weights is proposed. Finally, to address GDM challenges within hesitant-intuitionistic fuzzy scenarios, a novel decision method is presented. The validity of the proposed GDM approach is demonstrated through a case study involving the selection of outstanding students for exchange learning. Comparative analysis illustrates the method’s rationale and advantages.